Implementasi Tingkat Keasinan Telur Asin menggunakan Metode K-Nearest Neighbor dengan Sensor TCS3200 berbasis Arduino Mega - Rian Ari Hardianyah; Hurriyatul Fitriyah; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Salted eggs are one of the foods made from eggs that are preserved by salting. Most use duck eggs for preservation and it is possible to use other eggs. Salted eggs have different kinds such as boiled salted eggs, baked salted eggs, smoked salted eggs and grilled salted eggs. In detecting eggs that have been mashed and not mashed, the conventional method is still used. To distinguish between fried eggs and unmarried eggs, to determine the level of saltiness of salted eggs, the TCS3200 sensor will be used to detect the white and yolk colors. For the Arduino Mega Microcontroller, it is used for the proces implemented by the K-NN method to calculate the RGB result value. The results of the first TCS3200 obtained an average value of 4.05% while second TCS3200 obtained an average value of 8.34%. As for the accuracy of K-NN, the value is 66.67% where the difference is not too prominent so it is classified as good..